A near-infrared xanthene fluorescence probe for monitoring peroxynitrite in living cells and mouse inflammation model. Issue 22 (8th October 2018) - Wu, Yongquan; Shi, Aiping; Li, Yuanyan; Zeng, Hong; Chen, Xiaoyong; Wu, Jie; Fan, Xiaolin
Abstract : A novel near-infrared xanthene fluorescence probe for monitoring peroxynitrite in vitro and in vivo . Abstract : Peroxynitrite (ONOO − ) plays important roles in the regulation of many physiological and pathological processes, and an increase in its levels is related to numerous diseases. Thus, accurate detection of ONOO − in physiological conditions is imperative for elucidating its functions. However, studies on high signal-to-noise-ratio (SNR) fluorescence imaging of ONOO − in vivo for its detection are currently lacking. Thus, a novel NIR xanthene fluorescence probe (NOF2) for the endogenous detection of ONOO − is designed and synthesized. The fluorescence of the NOF2 probe is pre-quenched by the hydroxyl protection group of diphenyl phosphinate. Additionally, the NOF2 probe exhibits good selectivity and sensitivity for ONOO − with a low detection limit of 0.40 μM. Importantly, the NOF2 probe displays good performances for the detection of endogenous ONOO − not only in living cells but also in a mouse inflammation model. This demonstrates its great potential for applications involving the detection of ONOO − both in vitro and in vivo to explore the roles of ONOO − in different physiological systems.